Faktor yang Mempengaruhi Islamic Social Reporting pada Bank Umum Syariah di Indonesia Tahun 2014-2019 - Mei Rustiyani (Politeknik Negeri Medan, 2021)
ABSTRACK Sharia banks are expected to not only conduct business activities in accordance with sharia principles, but also be able to systematically disclose social responsibility in their annual reports. The purpose of this study is to analyze the influence of company size, profitability, sharia compliance, leverage and investment account holder. The population in this study were all sharia commercial banks that have been registered at OJK in Indonesia. The sample tested by 12 sharia commercial banks were selected using a purposive sampling method. The data collected in the form of annual report of sharia commercial banks from 2014 to 2019. The analytical method used in this research was descriptive statistical analysis and multiple linear regression analysis using Eviews 10 software. The result of study showed that size of company, profitability and investment account holder have a significant effect on the level of disclosure of Islamic Social Reporting. Meanwhile, sharia compliance and leverage do not have a significant effect of the level of disclosure of Islamic Social Reporting for sharia banks in Indonesia. Keywords: sharia banks, Islamic Social Reporting, Indonesia